A review of life cycle greenhouse gas (GHG) emissions of commonly used ex-situ soil treatment technologies. (10th June 2018) - Amponsah, Nana Y.; Wang, Junye; Zhao, Lian
Abstract: GHG emissions are important footprints because of increasing concern over climate change. Remediation methods produces GHGs in varying quantities based on which activities are involved through its entire life cycle and which contaminants are present, often because some contaminants are more difficult to remove from soil than others. Accounting for emissions from all phases of the project requires a life cycle assessment (LCA) approach. LCA can help in choosing the best available technology to reduce the environmental burden of the remediation technology or to improve the sustainability of the technology by implementing systematic approaches to ensure that future developments are optimized for environmental performance throughout the life cycle. The primary objective of this paper is to review existing LCA studies that report GHG emissions (CO2-eq ) or Global warming potential (GWP) from six ex-situ soil remediation technologies (ESRTs), including excavation and disposal, ex-situ thermal desorption, ex-situ soil vapor extraction, ex-situ bioremediation, excavation and incineration, and soil washing, and present the variability in GHG/GWP results and how this data can help in selecting an ex-situ soil remediation technology with a lower global warming potential. A second objective of this study is to compare the GWP levels of ex-situ remediation to the GWP levels of typical in situ remediation methods. Our results showed a large variation in GHG emissions of treated soil from six ESRTs varying from 3.1 × 10 −7  t to 8.2 t CO2 -eq/m 3 . Incineration had the highest mean GHG emissions (0.7 t CO2 -eq/m 3 ) and thermal desorption the lowest (0.07 t CO2 -eq/m 3 ). It was also found that there was a large variation range of GHG emissions from the ex-situ excavation and disposal method soil treatment technologies, varying from 3.1 × 10 −7  t to 8.2 t CO2 -eq/m 3 of treated soil. This knowledge provides opportunities to increase sustainability of soil remediation throughout the investigation, design, construction, operation, and monitoring phases of site remediation regardless of the selected cleanup remedy. This shows data on LCA GHGs are useful to assess the impact of different scenarios and management practices on ESRTs. Highlights: Review existing GHG emissions from six ex-situ remediation technologies (ESRTs). Use life cycle assessment as an effective tool for assessing GHG emissions of ESRTs. Collate and analyse the variability in GHG emissions from six ESRTs. Compare global warming impacts of six ESRTs with that of in-situ remediations. Incineration had the highest mean GHG emissions and thermal desorption the lowest.